Diversité des itinéraires migratoires des colons d’un front pionnier amazonien - Xavier Arnauld de Sartre; Pascal Sebille (Confins)
Even if the studies on migration have been organised from a long time around a debate between migrations caused by external events and family-based migration strategies, current research is seeking to establish the link between these two dynamic processes. The demographical life event history approach provided a statistical basis to bridge the gap between those two streams of research. But many explanations are still looking for a single explanation of many migrations. Our aim in this paper is to combine a spatial analysis to a life event history approach to build typologies of migrants. The Amazonian frontier is an adapted context for this problematic, since all its inhabitants are migrants. Their migrations are closely linked with the deforestations dynamics. That’s the reason why many researchers try to explain the reasons of their migration, but most of the time considering that the populations behave in a homogeneous manner. Based on a sample of 350 settlers encountered in recent colonised areas, our analysis shows the apparent homogeneity of the settler’s migrations, but stresses the diversity of their routes and of their logics of mobility – diversity which brings us to build a typology of those migrants based on their trajectories.